(untitled) (Malaysian Journal of Civil Engineering, 2018)
Load bearing capacity of subgrade soil is of great importance to the integrity of pavement. Soaked CBR of subgrade soil is used as a design parameter for determining the total thickness of a pavement for an estimated ESAL. However, determination of soaked CBR values for pavement design involves soaking a large number of representative soil samples for four days. This is both time consuming and economically discouraging. Establishment of mathematical models for determining soaked CBR values for different types of soils using their index properties, dry densities and unsoaked CBR values is likely to aid design more quickly. With this background in mind, in this study soil samples were collected from sub-grade of an existing flexible pavement in Savar Cantonment Area, Dhaka, Bangladesh. The soil samples were then tested and the index properties were determined. The tested soil samples were identified as Lean Clay and CBR test was performed both in soaked and unsoaked conditions at different densities. The test results of the sample soil have led to the formulation of three empirical equations for predicting soaked CBR values. Index properties of soil from grain size analysis, Atterberg limits test and compaction characteristics from CBR test are used in the first equation to predict soaked CBR value of this lean clay soil. The second equation relates dry density with soaked CBR whereas the third equation relates unsoaked CBR with soaked CBR values for a varying range of dry densities. These equations may be used to predict soaked CBR value where the sub-grade consists of Lean Clay.